2018
DOI: 10.1021/acs.orglett.7b03853
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Alkenyl Boronates from Epoxides with Di-[B(pin)]-methane via Pd-Catalyzed Dehydroboration

Abstract: A practical and broadly applicable catalytic method for the synthesis of (E)-alkenylborons is presented. Reactions are promoted by [Pd(Cl)(η-CH)] and proceed by the dehydroboration of cyclic borates. Through the use of epoxides and readily available di-B(pin)-methane (pin = pinacolato), a range of allylic alcohol-containing alkenyl boronates, including those that contain a tertiary alcohol, may be prepared in up to 75% yield and >20:1 E/Z.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(23 citation statements)
references
References 39 publications
0
20
0
Order By: Relevance
“…The reactivity explored with diborylmethide lithium salts for C−C bond formation involves alkylation reactions with aryl‐ or alkyl halides (Scheme a) as well as boron‐Witting reactions with carbonyl compounds (Scheme b). The reactivity of diborylmethide lithium salts with electrophiles other than aldehydes/ketones or RX has not been explored, except for an attempt to contribute to the copper‐catalyzed one‐pot three‐component stereoselective coupling of epoxides with allyl electrophiles and bis[(pinacolato)boryl]methane (Scheme c) or palladium‐catalyzed coupling/dehydroboration (Scheme c)…”
Section: Methodsmentioning
confidence: 99%
“…The reactivity explored with diborylmethide lithium salts for C−C bond formation involves alkylation reactions with aryl‐ or alkyl halides (Scheme a) as well as boron‐Witting reactions with carbonyl compounds (Scheme b). The reactivity of diborylmethide lithium salts with electrophiles other than aldehydes/ketones or RX has not been explored, except for an attempt to contribute to the copper‐catalyzed one‐pot three‐component stereoselective coupling of epoxides with allyl electrophiles and bis[(pinacolato)boryl]methane (Scheme c) or palladium‐catalyzed coupling/dehydroboration (Scheme c)…”
Section: Methodsmentioning
confidence: 99%
“…With optimized conditions,weembarked on astudy of the generality of this reaction. As shown in Table 2, arylboronic esters (entries 6-9)u nderwent the reaction in useful efficiency,a nd showed that the reaction tolerates both electrondonating and electron-withdrawing groups.A lkylboronic esters also proved to be competent substrates but benefitted from modified reaction conditions.I naprevious study, [9] the addition of DMSO as ac o-solvent was found to stabilize the "ate" complex formed from alkylboronic esters and Grignard reagents and this modification proved helpful to the reaction of the substrates here as well. However,t he addition of DMSO retarded the reaction rate and 18 hours were required for these reactions to reach completion.…”
mentioning
confidence: 94%
“…[8] In this manuscript, we present ar eaction design that allows Pd(allyl) electrophiles to activate alkenylboron "ate" complexes for the metallate shift reaction. While this activation mechanism has been employed in the context of conjunctive cross-coupling reactions,w ed emonstrate herein that the catalytic intermediate can be diverted towards b-hydride elimination, [9] which establishes an alkene while leaving the original boronic ester group intact [Eq. (3)].…”
mentioning
confidence: 99%
“…Alternatively, gem-diborylalkanes have also been used to generate (gem-diborylalkyl)lithiums by treatment with as terically hindered amide base (Scheme 1b). [9] More recently,t he group of Pattison reported aconvenient method to generate boron enolates by reacting esters with (gem-diborylalkyl)lithiums,w hich could be trapped by an electrophile to afford a,a-difunctionalized ketones. [8] Meek et al disclosed ah ighly stereoselective addition of generated (diborylmethyl)lithium to enantioenriched epoxides to obtain fivemembered cyclic boronates and their practical use in the copper-catalyzed stereospecific deborylative coupling with allylic electrophiles.…”
mentioning
confidence: 99%
“…[8] Meek et al disclosed ah ighly stereoselective addition of generated (diborylmethyl)lithium to enantioenriched epoxides to obtain fivemembered cyclic boronates and their practical use in the copper-catalyzed stereospecific deborylative coupling with allylic electrophiles. [9] More recently,t he group of Pattison reported aconvenient method to generate boron enolates by reacting esters with (gem-diborylalkyl)lithiums,w hich could be trapped by an electrophile to afford a,a-difunctionalized ketones. [10] Despite this progress,t he current utilization of (gem-diborylalkyl)metallics relies primarily on the use of in situ generated (gem-diborylalkyl)lithiums.…”
mentioning
confidence: 99%